The Language of Jokes in the Digital Age Viral Humour - Chiaro, Delia (Taylor & Francis, 2018)
In this accessible book, Delia Chiaro provides a fresh overview of the language of jokes in a globalized and digitalized world. The book shows how, while on the one hand the lingua-cultural nuts and bolts of jokes have remained unchanged over time, on the other, the time-space compression brought about by modern technology has generated new settings and new ways of joking and playing with language. The Language of Jokes in the Digital Age covers a wide range of settings from social networks, e-mails and memes, to more traditional fields of film and TV (especially sitcoms and game shows) and advertising. Chiaro's consideration of the increasingly virtual context of jokes delights with both up-to-date examples and frequent reference to the most central theories of comedy. This lively book will be essential reading for any student or researcher working in the area of language and humour and will be of interest to those in language and media and sociolinguistics.